Narrative means to journalistic ends a narratological analysis of selected journalistic reportages - Berning, Nora; SpringerLink (Online service). (Wiesbaden VS, Verlag für Sozialwissenschaften, 2011)
Nora Berning grasps the narrative potential of journalistic reportages via a set of narratological categories. Spurred by an interdisciplinary framework, she builds on transgeneric narratological research and shows that journalistic reportages can be described, analyzed, and charted with categories that originate in structuralist narratology. The author spells out minimal criteria for particular types of reportages, and challenges the argument that journalism and literature have distinct, non-overlapping communicative goals. By showing that the reportage is a hybrid text type that seeks to inform, educate, and entertain, this study advances a re-conceptualization of journalism and literature as two fields with permeable borders. The book is written for researchers and students in the fields of journalism, media, communications, and literary theory.
Contents Part I: Theoretical Framework -- Narratology: The Systematic Analysis of Narratives -- The Journalistic Reportage and its Narrative Potential -- State of Research: Literature Review Part II: Empirical Analysis -- Research Design: The Methodological Framework -- Results of the Empirical Study Part III: Discussion and Outlook -- Critical Reflections on the Results
Electronic reproduction.
Keywords: Journalism and literature; Journalism -- Technique; Narration (Rhetoric); Electronic books